Achieving Over 15% Efficiency in Organic Photovoltaic Cells via Copolymer Design. Issue 14 (19th February 2019) - Cui, Yong; Yao, Huifeng; Hong, Ling; Zhang, Tao; Xu, Ye; Xian, Kaihu; Gao, Bowei; Qin, Jinzhao; Zhang, Jianqi; Wei, Zhixiang; Hou, Jianhui
Abstract: Ternary blending and copolymerization strategies have proven advantageous in boosting the photovoltaic performance of organic solar cells. Here, 15% efficiency solar cells using copolymerization donors are demonstrated, where the electron‐withdrawing unit, ester‐substituted thiophene, is incorporated into a PBDB‐TF polymer to downshift the molecular energy and broaden the absorption. Copolymer‐based solar cells suitable for large‐area devices can be fabricated by a blade‐coating method from a nonhalogen and nonaromatic solvent mixture. Although ternary solar cells can achieve comparable efficiencies, they are not suitable for environment‐friendly processing conditions and show relatively low photostability compared to copolymer‐based devices. These results not only demonstrate high‐efficiency organic photovoltaic cells via copolymerization strategies but also provide important insights into their applications in practical production. Abstract : Organic solar cells achieve over 15% efficiency through the use of a copolymer donor, and simultaneously enhanced open‐circuit voltage and short‐circuit current density are obtained. High‐performance solar cells are adaptable for environment‐friendly solvents using a blade‐coating method, while showing better photostability than the corresponding ternary solar cells.